Efektivní design dodavatelských systémů - Škvor, Jan; Dyntar, Jakub; Gros, Ivan (Univerzita Pardubice, 2011)
In this paper we present the efficient approach to design of supply chains based on warehouse location. We propose two methods of warehouse location such as the localization method and total enumeration method and compare their efficiency in a numerical study. Based on the results of the numerical study we conclude that both proposed solutions can be used for efficient warehouse location in case of one warehouse placement. In case of the location of many warehouses we recommend the application of localization method mainly because of the acceptable time consumption spent on the searching for the optimal solution.
Keywords: distribution; supply chain design; warehouse location